GERAKAN MASYARAKAT ADAT SAMI DAN KONTESTASI SUMBER DAYA ALAM - Manggala Ismanto (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2017)
The main agenda of the indigenous movement is fighting for political and cultural rights of ethnic minority communities in accordance with unique historical and cultural practices that they have. As Kymlicka said, minority rights must also be fought because they are on a system that is governed by the majority who pretend to produce injustice. Sami Indigenous Movement in Norway is a form of a long struggle to obtain the right independently to manage natural resources. Currently Sami struggling to maintain the uniqueness of the cultural identity and living practices that have been owned for generations. This paper would like to see the establishment of indigenous peoples' movement Sami in Norway as well as the practice of social movements committed to demanding social change related to self-governance and autonomy of management of natural resources.Keywords: Indigenous Movement, Sami People, Identity, Otonomy,Natural Resource ManagementAbstrakAgenda utama dalam gerakan adat atau indigenous movement adalah memperjuangkan hak politik dan budaya komunitas etnis yang menjadi minoritas sesuai dengan keunikan historis serta praktik budaya yang mereka miliki. Seperti yang dikatakan oleh Kymlicka, bahwa hak-hak minoritas juga harus diperjuangkan karena mereka berada pada sistem yang diatur oleh mayoritas yang berpretensi menghasilkan ketidakadilan. Gerakan Masyarakat Adat Sami di Norwegia merupakan bentuk perjuangan panjang untuk memperoleh hak secara mandiri untuk mengelola sumber daya alam. Saat ini masyarakat Sami berjuang untuk mempertahankan keunikan identitas budaya dan praktik hidup yang telah dimiliki secara turun temurun. Tulisan ini ingin melihat pembentukan gerakan masyarakat adat Sami di Norwegia serta praktik gerakan sosial yang dilakukan untuk menuntut perubahan sosial terkait dengan self-governancedan otonomi pengelolaan sumber daya alam.Kata kunci: Gerakan Masyarakat Adat, Sami, Identitas, Otonomi, Pengelolaan Sumber DayaAlam